Perlindungan Hak Tersangka Dan Terdakwa: Penegakan Prinsip Fair Trial dalam Sistem Peradilan Pidana - Putu Sekarwangi Saraswati (Faculty of Law, Mahasaraswati University, Denpasar, 2025)
The Unitary State of the Republic of Indonesia as a constitutional state (rechtstaat) based on Pancasila means that Pancasila is the source of all laws applicable in this country. All citizens within a constitutional state, without exception, are treated equally before the law (Equality Before The Law). They are entitled to recognition and human rights, whereby all people have the right to be treated equally. One of these rights is the right to a fair trial, which is an important part of human rights, recognized in both national and international law. In the 1945 Constitution itself, this is stated in Article 24 paragraph (1), which states that “Judicial power is an independent power to administer justice in order to uphold law and justice” and Article 28 D paragraph (1), which states that